INTENSIVE TECHNOLOGY FOR RAISING HEIFERS OF IMPORTED CATTLE. (Scientific journal of the Fergana State University, 2023)
The article highlights that the feeding of imported heifers with rapeseed (colza) flour used as forage crops in the amount of 15% of the protein content in the ration had a positive effect on metabolic processes and led to an intensive average daily gain in live weight.